Ensaios bioquímicos e celulares para a identificação de novos inibidores de TcGAPDH seletivos à HsGAPDH - Soares, Fabyana Aparecida (Universidade Federal de São Carlos, 2011)
Chagas disease is a tropical neglected illness; nearly 10 million people are infected, in 2008 it was responsible for the deaths of about 10 thousand people. At present, only two medicines (benznidazol and nifurtimox) are available to treat this disease and they lack of efficacy/safety in chronic phase. This scenario is changing due to advances in the search for new trypanocidal agents. The glyceraldehyde-3-phosphate dehydrogenase (GAPDH), a glycolytic enzyme of Trypanosoma cruzi appears as a suitable target for drug discovery. In the present work, a kinetic study using Isothermal Titration Calorimetry (ITC) were carried out to investigate the activity of eight NAD+ analogs against GAPDH. ITC was been used to measure the heat exchange during reactions making it a powerful tool of identification of bioactive compounds. Study compounds showed inhibitory activity on TcGAPDH enzyme and its homologous human GAPDH. The apparent inhibition constant values (Ki app) were in the range from 15,98 to 91,25 M describing competitive inhibition mechanisms. Important steps in medicinal chemistry maybe biochemical followed by cell-based assays were, for instance, Saccharomyces cerevisiae could be used as a model to assess the cytotoxic activity of compounds. The technique used to study the action of chemical compounds in yeast was the fluorescence spectroscopy. Five out of eight compounds showed no activity against S. cerevisiae. This is a good indication that study compounds have low cytotoxicity, which makes them candidates for in vitro studies on the parasite.
Keywords: Química orgânica; Calorimetria de titulação isotérmica; Chagas, Doença de; GADPH; CIENCIAS EXATAS E DA TERRA::QUIMICA